Modulation of synaptic transmission in hippocampal CA1 neurons by a novel neurotoxin (beta-pompilidotoxin) derived from wasp venom - Yokota, Hidenori; Tsubokawa, Hiroshi; Miyawaki, Takahiro; Konno, Katsuhiro [UNESP]; Nakayama, Hitoshi; Masuzawa, Toshio; Kawai, Nobufumi (Elsevier B.V., 2001)
We examined the effects of beta-pompilidotoxin (beta-PMTX), a neurotoxin derived from wasp venom. on synaptic transmission in the mammalian central nervous system (CNS). Using hippocampal slice preparations of rodents, we made both extracellular and intracellular recordings from the CA1 pyramidal neurons in response to stimulation of the Schaffer collateral/commissural fibers. Application of 5-10 muM beta-PMTX enhanced excitatory postsynaptic potentials (EPSPs) but suppressed the fast component of the inhibitory postsynaptic potentials (IPSPs). In the presence of 10 muM bicuculline, beta-PMTX potentiated EPSPs that were composed of both non-NMDA and NMDA receptor-mediated potentials. Potentiation of EPSPs was originated by repetitive firings of the prosynaptic axons, causing Summation of EPSPs. In the presence of 10 muM CNQX and 50 muM APV, beta-PMTX suppressed GABA(A) receptor-mediated fast IPSPs but retained GABA(B) receptor-mediated slow IPSPs. Our results suggest that beta-PMTX facilitates excitatory synaptic transmission by a presynaptic mechanism and that it causes overexcitation followed by block of the activity of some population of interneurons which regulate the activity of GABA(A) receptors. (C) 2001 Published by Elsevier B.V. Ireland Ltd and the Japan Neuroscience Society.
Keywords: Beta-PMTX; Hippocampal slice; Neurotoxin; Wasp venom; 2 amino 5 phosphonovaleric acid; 4 aminobutyric acid A receptor; 4 aminobutyric acid receptor blocking agent; 6 cyano 7 nitro 2,3 quinoxalinedione; Amino acid receptor blocking agent; Benzyl[3 [[1 (3,4 dichlorophenyl)ethyl]amino] 2 hydroxypropyl]phosphinic acid; Bicuculline; Bicuculline methochloride; Drug derivative; N methyl dextro aspartic acid receptor; Neurotoxin; Phosphinic acid derivative; Pompilidotoxin beta; Propanolamine derivative; Receptors, GABA A; Receptors, N Methyl D Aspartate; Wasp venom; Action potential; Animal; Chemistry; Classification; Comparative study; Cytology; Dendrite; Drug effect; Excitatory postsynaptic potential; Gerbil; Hippocampus; Interneuron; Isolation and purification; Nerve cell; Physiology; Pyramidal nerve cell; Rat; Rat strain; Sodium channel; Synaptic transmission; 2-Amino-5-phosphonovalerate; 6-Cyano-7-nitroquinoxaline-2,3-dione; Action Potentials; Animal; Bicuculline; Comparative Study; Dendrites; Excitatory Amino Acid Antagonists; Excitatory Postsynaptic Potentials; GABA Antagonists; Gerbillinae; Hippocampus; Interneurons; Neurons; Neurotoxins; Phosphinic Acids; Propanolamines; Pyramidal Cells; Rats; Rats, Wistar; Receptors, GABA-A; Receptors, N-Methyl-D-Aspartate; Sodium Channels; Support, Non-U.S. Gov't; Synaptic Transmission; Wasp Venoms